Circulation of Lassa virus across the endemic Edo-Ondo axis, Nigeria, with cross-species transmission between multimammate mice - Adetunji Samuel Adesina; Akinlabi Oyeyiola; Adeoba Obadare; Joseph Igbokwe; Chukwuyem Abejegah; Patience Akhilomen; Umaru Bangura; Danny Asogun; Ekaete Tobin; Olufemi Ayodeji; Omolaja Osoniyi; Chris Davis; et al. (Emerging Microbes and Infections)
We phylogenetically compared sequences of the zoonotic Lassa virus (LASV) obtained from Mastomys rodents in seven localities across the highly endemic Edo and Ondo States within Nigeria. Sequencing 1641 nt from the S segment of the virus genome, we resolved clades within lineage II that were either limited to Ebudin and Okhuesan in Edo state (2g-beta) or along Owo-Okeluse-Ifon in Ondo state (2g-gamma). We also found clades within Ekpoma, a relatively large cosmopolitan town in Edo state, that extended into other localities within Edo (2g-alpha) and Ondo (2g-delta). LASV variants from M. natalensis within Ebudin and Ekpoma in Edo State (dated approximately 1961) were more ancient compared to those from Ondo state (approximately 1977), suggesting a broadly east-west virus migration across south-western Nigeria; a pattern not always consistent with LASV sequences derived from humans in the same localities. Additionally, in Ebudin and Ekpoma, LASV sequences between M. natalensis and M. erythroleucus were interspersed on the phylogenetic tree, but those from M. erythroleucus were estimated to emerge more recently (approximately 2005). Overall, our results show that LASV amplification in certain localities (reaching a prevalence as high as 76% in Okeluse), anthropogenically-aided spread of rodent-borne variants amidst the larger towns (involving communal accommodation such as student hostels), and virus-exchange between syntopic M. natalensis and M. erythroleucus rodents (as the latter, a savanna species, encroaches southward into the degraded forest) pose perpetual zoonotic hazard across the Edo-Ondo Lassa fever belt, threatening to accelerate the dissemination of the virus into non endemic areas.